Prototype Sistem Informasi Presensi Karyawan Dengan Pendeteksi Lokasi Berbasis Web Pada PT Space Indonesia - Danendra Saskara; Budi, Budi; Rahmadi (Ikatan Ahli Informatika Indonesia, 2025)
PT Space Indonesia, located in the EJIP area of South Cikarang, Bekasi Regency, currently uses a fingerprint-based employee attendance system. This system faces several issues, including dependence on electricity, frequent maintenance, and malfunction due to dirty or wet sensors. Moreover, it does not support digital submission of leave, sick, or permission requests, making attendance administration less efficient. This study aims to design a web-based employee attendance information system equipped with location detection features using Geotagging and GPS technology. The system enables employees to check in online via PC, laptop, or smartphone, whether working on-site or remotely (Work From Anywhere). It also includes features for submitting leave, sick, and permission requests, as well as exporting attendance reports in Excel and PDF formats. Data collection was conducted through observation and interviews with the HR and IT staff. The system was developed using the Prototype method with a UML design approach and built using Laravel 11, Laravel Filament, PHP, HTML, CSS, JavaScript, and MySQL, running on Laragon. The result is a web-based attendance system prototype that offers greater flexibility and efficiency compared to conventional fingerprint systems.